Empirical Analysis of Poverty Dynamics: With Case Studies from Sub-Saharan Africa - Isabel Günther (Peter Lang International Academic Publishers, 2007)
The empirical analysis of poverty over time is still severely constrained by the available survey data in developing countries. In the past, this has led to a neglect of certain aspects of poverty dynamics or even biased assessments of poverty dynamics. This book explicitly takes into account the present data limitations, proposing alternative methods for the empirical analysis of poverty dynamics. The work addresses both the problems related to limited data in the analysis of macro-level (or national) as well as micro-level (or household) poverty dynamics. The proposed methods are applied to survey data from various sub-Saharan African countries. As these countries do not only have the most limited economic survey data but also show the highest poverty rates in the world an accurate understanding of the underlying poverty dynamics seems to be most important for these countries.
Keywords: 330